Perceived compliance and knowledge of Title IX in physical education and athletics - Irwin, Laurie M. (My University, 1981)
The purpose of this study was to determine the effect of sex and professional role on perceived compliance with and actual knowledge of Title IX in physical education and athletics. Administrators (Title IX coordinators, physical education supervisors, and athletic directors), physical education teacher/coaches (physical education teachers and physical education teacher/coaches), and coaches (N = 69) were administered the Title IX Implementation Assessment Instrument and the Title IX Knowledge Instrument. Each instrument had a section for physical education and athletics. Ss responded to the instruments in the following four areas: perceived compliance with physical education, perceived compliance with athletics, knowledge in physical education, and knowledge in athletics. A two-way ANOVA was used to determine differences in each of the four measures. Spearman's Rho Correlation Coefficient was used to test the relationship between perceived compliance and knowledge for physical education and athletics. Results indicated that females perceived physical education and athletic programs to be significantly less in compliance with Title IX than did their male counterparts. Females also scored significantly higher on the physical education portion of the Title IX Knowledge Instrument. The results of the Scheffe test indicated that teacher/coaches were scored significantly lower than administrators and coaches on knowledge of Title IX in athletics. Significant sex by role interaction was also evident in Title IX knowledge of athletics with female teacher/coaches being significantly less knowledgeable than male coaches, male administrators, female coaches, and female administrators. Results of all other F-tests were not significant. Spearman's Rho revealed no significant relationship between perceived compliance and actual knowledge of Title IX for physical education or athletics.
Keywords: Physical education teachers -- Wisconsin -- Milwaukee County -- Attitudes